The Atomic Structure Learning System With Flipped Guided Inquiry on Discord: A Development Study - Santia, Andini; Mawardi, Mawardi; Suryani, Okta; Akmar, Reza (PT Inovasi Pratama Internasional, 2025)
This study aims to develop a Flipped Classroom learning system based on Guided Inquiry using the Discord application on the Atomic Structure material to improve the understanding of high school students, tested up to the validity and practicality stages. The product is considered valid if the validity score (V) is above 0.8 and highly practical if the practicality percentage score exceeds 86%. The method used in this study is Educational Design Research (EDR) with the Plomp model. In the development stage, formative evaluation was conducted through four prototypes. The first prototype was developed based on needs analysis, context analysis, and literature study. The second and third prototypes were refined through expert review and one-to-one evaluation, with results showing excellent content and construct validity. The research subjects consisted of 3 chemistry lecturers from UNP. Meanwhile, the practicality test on the fourth prototype, which involved teachers and students, showed that this learning system was highly practical, with 2 chemistry teachers and 9 students from SMAN 8 Padang. The data collection instruments used in this study were validity and practicality test questionnaires. Based on the results, a validity score of 0.86 and a practicality score of 92% were obtained, indicating that the system is valid and highly practical.